PERKEMBANGAN JUMLAH FRAKSI DPR RI MASA ORDE BARU HINGGA REFORMASI (1966-2004) - Rismauli Simbolon; Yohana Fransisca Br Karo; Timotius Agriva Tarigan; Roberson Dongoran; Roberto Simbolon (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
The function of the House of Representatives as stated in the 1945 Constitution of the Republic of Indonesia Article 20A paragraph (1) is a legislative function, a budget function and a supervisory function. The provisions in the 1945 Constitution were then translated into Law Number 22 of 2003 concerning the Structure and Position of the MPR, DPR, DPD and DPRD. The House of Representatives (DPR) in Indonesia has experienced many ups and downs. At least it is divided into 3 (three) periods, namely the Old Order, New Order and Post New Order or Reformation periods. However, in this paper the researcher only discusses the New Order and Post-New Order or Reformation periods. At the beginning of the New Order government, the DPR underwent several changes, both regarding its membership and authority. This research is entitled "Differences in the Membership Structure of the DPR in the New Order Period and the 1966-2004 Reformation Period." using historical research methods which include heuristics, verification, interpretation, historiography. In the composition of the membership of the New Order DPR from 1971 to 1977 the role of the People's Representative Council was more to support the executive than as a supervisor. The period 1971-1977 was different from the previous year's period. During the New Order period of 1966-1977 there were 9 political parties that existed during the New Order era, namely Parmusi, NU, PSII, Perti, PNI, Catholic Party, PARKINDO, IPKI, and Murba. In the composition of the New Order DPR membership from From 1971 to 1977 the role of the People's Representative Council was more to support the executive than as a supervisor. The 1971-1977 period had a difference from the previous year's period, in which during this period it provided a place for members who were appointed to the DPR, such as ABRI and Golkar